Dyslipidemia in the pediatric population. Relevance of early diagnosis and treatment (Archives of Pediatrics of Uruguay, 2021)
Publicado anteriormente en la Revista Uruguaya de Cardiología 2019; 34:313-323doi: 10.29277/cardio.34.3.20
Keywords: Dyslipidemia; Hypercholesterolemia; Hypertriglyceridemia; Cardiovascular risk; Pediatrics